EFEKTIVITAS ORICNET DALAM MENGENDALIKAN KUMBANG TANDUK DI KELAPA SAWIT FASE TBM - Andre Natama Hasibuan; Rizki Habib Alhabsi; Muhammad Fakhrurozi; Rudi Rahayu; Muhammad Jafar Abdillah; Muhammad Dzaikra Prayoga (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Rhinoceros rhinoceros is a significant threat that targets juvenile oil palm trees, particularly in newly replanted locations, potentially leading to a plant death rate of as much as 25%. This research seeks to evaluate how well the Oricnet technique serves as a physical barrier to manage rhinoceros beetle invasions on oil palm trees during the Immature Plant stage. The study was conducted in April 2026 at the community plantation of Sialtong Village, Serdang Bedagai Regency, North Sumatra, using a Non-Factorial Randomized Block Design (RAK) with two treatments: without net span (P0) and using net span (P1). The results showed that the use of net span had a significant effect on reducing the number of pest attacks. The average attack intensity in the treatment with nets (P1) was 18.16%, lower than the control (P0) which reached 27.66%. The net span method was proven to have a control effectiveness value of 34.35% in suppressing rhinoceros beetle attacks. The use of nets acts as a mechanical barrier that limits the access of adults to plant shoots, making it an environmentally friendly control solution by reducing reliance on chemicals.